Determinants of Stunting at 6 Weeks in the Northern Cape Province, South Africa - le Roux, Maretha; Nel, Mariette; Walsh, Corinna (Frontiers in Public Health, 2020)
The first 1,000 days from conception to 24 months is a critical period for healthy growth and development. In South Africa, stunting (weight-for-length below −2SD from the WHO reference mean) is a major public health issue with significant health consequences. We determined associations between demographic, health, and anthropometric indicators of mothers and their infants. A cross-sectional study was conducted in the Northern Cape. All mothers with 5- to 7-week-old babies visiting PHC facilities were invited to participate. A questionnaire was completed in a structured interview with each mother. Age and length of the baby at 6 weeks were used to determine stunting, while the weight and height of the mother were measured for body mass index (BMI). Eight hundred questionnaires were completed in 92 facilities. The median age of mothers was 26 years (IQR 20–30 years) and 44.9% were married. Only 40.1% had completed school or tertiary education and almost 40% relied on a government grant as the main source of income. Two-thirds (64.9%) had not planned the pregnancy and 17% were on antiretroviral therapy (ART). More than a quarter (26.1%) smoked cigarettes or used snuff during pregnancy, while 9.4% drank alcohol. At 6 weeks, 31% of boys and 14% of girls had a length-for-age below the WHO reference values, while 25.4% of mothers were classified as obese and 24.6% as overweight. More than 70% had a waist circumference above 80 cm. Significantly more mothers with stunted babies weighed less [−6 kg; −1 kg] and were shorter [−4 cm; −1 cm] than mothers with babies who were not stunted. Compared to babies who were not stunted, significantly more babies of mothers who lived in informal housing [−19.7%; −3.2%], relied on a grant [−19.7%; −3.2%], smoked/ snuffed [7.6%; 23.5%], and used alcohol during pregnancy [0.3%; 11.5%] were stunted. The following factors significantly increased the risk of having a stunted baby at 6 weeks: living in informal housing vs. formal housing (RR: 0.68, 95% CI [0.5; 0.9]); smoking or using snuff during pregnancy (RR: 1.74, 95% CI [1.3; 2.3]); using alcohol during pregnancy (RR: 1.5, 95% CI [1.1; 2.2]); both smoking and using alcohol during pregnancy (RR: 1.97, 95% CI [1.4; 2.9]). We confirmed the coexistence of under- and over-nutrition among mothers and their babies, possibly indicating that stunting in childhood may predispose to overweight and obesity in adulthood in a vicious cycle that affects generation after generation. Interventions aimed at poverty alleviation and encouraging healthy lifestyles with an emphasis on healthy eating, smoking cessation and abstaining from alcohol before pregnancy are urgently required.